[Page - (:unkn) unknown (G. Nicol; J. Murrary; and W. Wilson, Dublin, 1778)
"A new & accurate map of the kingdom of Ireland," by Taylor & Skinner.
Taylor and Skinner?s maps of the roads of Ireland
Keywords: Real property -- Ireland -- Maps; Ireland --Road maps -- to 1800